Using drawings to explore future orientation and hope among adolescent refugees : a case study of Syrian refugees in Malaysia - Ahmed, Iman Osman Mukhtar (Kulliyyah of Education, International Islamic University Malaysia, 2017)
Syrian Adolescent Refugees (SARs), who have fled 'war-torn' Syria, arrived in Malaysia where they have faced many challenges affecting them physically and psychologically. This study aims to explore the effectiveness of using SARs' drawings and interviews to better understand their future orientation and hope within the context of the bio-ecological system. It also aims to address the nature of the adolescents and their reciprocal interaction relationships within their bio-ecological context and their effect on the adolescents' future orientation, hope, adjustment and coping within the new environment. The bio-ecological theory serves as the theoretical and conceptual framework of the study. A case-study qualitative research approach was utilized using the drawing and interviews as instruments to collect the data from eleven (11) SARs in Malaysia who were under the authority of UNHCR. The thematic content analysis was utilized to analyse the collected data. The findings revealed that the SARs did not have negative expectations about their future because they had goals and plans for the future. SARs faced several challenges that had a negative impact on their life and their ability to achieve their future goals, but they still have remained determined to accomplish their goals. The support of the parents, peers, significant others, and the community played a highly significant role in helping and encouraging SARs to hold on to their future plans, continue to have hope, cope with the war trauma and adjust to the new society. Several traumatic symptoms were projected in the participants' Peace and War drawings. The SARs used many coping strategies to come to terms with the new environment such as improving their personal traits, spirituality and religiosity and mixing with local community and communicating with international friends and their families through social media. The study also supports the use of the bio-ecological theory as a framework to study the situations of refugees from different perspectives. 'Draw Your Self Now' and 'Draw Your Self in the Future' assessment tools can be utilized as art therapy which provide precious information about adolescents' feelings pertaining their present and future selves. This study is significant in filling the existing research gap as it emphasizes on the importance of future and hope. It also serves as a reference for intervention programs, educators and psychologists.